2021
DOI: 10.1186/s13027-021-00390-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive high-throughput meta-analysis of differentially expressed microRNAs in transcriptomic datasets reveals significant disruption of MAPK/JNK signal transduction pathway in Adult T-cell leukemia/lymphoma

Abstract: Background Human T-lymphotropic virus 1 (HTLV-1) infection may lead to the development of Adult T-cell leukemia/lymphoma (ATLL). To further elucidate the pathophysiology of this aggressive CD4+ T-cell malignancy, we have performed an integrated systems biology approach to analyze previous transcriptome datasets focusing on differentially expressed miRNAs (DEMs) in peripheral blood of ATLL patients. Methods Datasets GSE28626, GSE31629, GSE11577 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…MiRNAs deregulated by HTLV-1 have been identified in recently published studies [ 5 , 28 , 35 , 36 , 37 , 38 , 39 ]. Interestingly, none of the eight miRNAs identified in our study were described to be deregulated in the presence of HTLV-1 or in subjects with ATL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs deregulated by HTLV-1 have been identified in recently published studies [ 5 , 28 , 35 , 36 , 37 , 38 , 39 ]. Interestingly, none of the eight miRNAs identified in our study were described to be deregulated in the presence of HTLV-1 or in subjects with ATL.…”
Section: Discussionmentioning
confidence: 99%
“…While MiRNA profiling has been extensively investigated in the context of HTLV-1 infection [ 5 , 28 , 35 , 36 , 37 , 38 , 39 ], evidence of HTLV-2’s impact on the miRNA expression is almost absent, except for only one study, which reported a profile of eight miRNAs common to both CD4+ T cells from HTLV-2 and HIV-1 mono-infected patients [ 40 ]. In the case of HTLV-1, alteration of the miRNA expression has been shown to be associated with the development of ATL and HAM/TSP disorders [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of chemotherapy drugs and miRNAs can be a suitable remedy for ATLL [9]. Several papers have introduced the genes and miRNAs implicated in the progression of ATLL without considering different subtypes [10][11][12]. Therefore, the exploration of miRNA-gene interactions in various ATLL subtypes to propose potential therapeutic targets using computational algorithms could be advantageous.…”
Section: Introductionmentioning
confidence: 99%